Statistična poslovna analiza: Gradiva za seminarske in laboratorijske vaje - Tominc, Polona; Rožman , Maja (University of Maribor Press, 2021)
Statistical Business Analysis: Seminar and Laboratory Tutorials. The Statistical Business Analysis contains the following chapters: descriptive statistics and probability sampling, hypothesis testing about statistically significant differences between the arithmetic means ​​of a variable in several samples and regression analysis. Within the course to which these tutorials refer, students learn about the usefulness of statistical methods in solving business problems and consolidate and upgrade theoretical knowledge in the field of statistical techniques and methods that allow to change various data into useful information for business decision making. Students acquire an analytical mathematical-statistical view to the study of business problems, which consists of the following steps: formulation of the problem in a statistical way, selection of appropriate statistical methods, problem solving and interpretation of results in terms of possible solutions. In these tutorials we describe some statistical quantitative methods that are tools in business research, using the IBM SPSS software.